Kontestasi Politik Suku Batak Toba: Pemilihan Kepala Desa di Desa Pala Pulu Tahun 2023 - Purba, Ririn (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Provinsi Sumatera Utara, 2025)
The Batak Toba ethnic group in Pala Pulu Village serves as the focal point of this study due to its deep-rooted cultural and social capital dynamics. Political brokers play a crucial role as mediators between candidates and the community. While brokers are often perceived as being driven solely by material interests, this is not always the case. Thus, how do brokers interact with electoral processes among the Batak people in their homeland? This study aims to illustrate the complexity of brokers' involvement in securing electoral victories. Using a descriptive qualitative approach, the findings indicate that Putnam's (1993) concept of social capital remains essential for garnering votes. Clan affiliations function as social networks, and trust cultivated over time serves as a significant asset in the village head election contestation among the Batak Toba people in Pala Pulu Village. Meanwhile, money politics still exists but is no longer a dominant or alarming factor, as public awareness and knowledge have significantly improved. In practice, brokers continue to be involved in village politics. However, in Pala Pulu Village, brokers now act as assemblers—constructing networks of new brokers for broader political contestations. This phenomenon is closely linked to the upcoming regional elections in 2024. Keywords: village head election, the batak toba, political contestation, political broker, electoral strategy